ANALISIS CIKAL BAKAL SISTEM PEREKONOMIAN ISLAM - Andi Cahyono; Uswatun Hasanah (Program Studi Ekonomi Syariah, 2022)
This study aims to determine the forerunner of the Islamic economic system. The research method used is qualitative research with a research approach (library research). The results of this study indicate that the Islamic economy has started since the Prophet Muhammad SAW served as head of state in Madina, then he made changes to the state's economic and financial system in accordance with the provisions of the Qur'an of the Prophet Muhammad SAW formed the Baitul al Mal, namely all results The collection of state assets is collected first, then issued according to the needs of the state. State income comes from kharaz, zakat, khusz, Jizyah, and other receipts such as kaffarah and inheritance of people who do not have heirs. As for fiscal policy in the early days of Islam, it can be seen that zakat played a very important role in achieving the objectives of fiscal policy, namely to finance government spending and to perform regulatory functions in order to achieve certain economic goals, such as economic growth and the creation of investment and employment. This is not much different from the function of taxes in modern fiscal policy. Therefore, zakat and taxes have similarities in their position in fiscal policy.